Combined effect of marriage and education on mortality: A cross-national study of older Japanese and Finnish men and women - Tami Saito; Tuula Oksanen; Kokoro Shirai; Takeo Fujiwara; Jaana Pentti; Jussi Vahtera (Japan Epidemiological Association, 2022)
Background: While marriage and education help maintain older adults’ health, their joint association with mortality remains unclear. This cross-national study examined the combined effect of marriage and education on the mortality of older Japanese and Finnish adults.
Methods: Data on 22,415 Japanese and 11,993 Finnish adults, aged 65–74 years, were obtained from the Japan Gerontological Evaluation Study of 2010–2012 and the Finnish Public Sector Study of 2008–2009 and 2012–2013. We followed up on respondents’ survival status for 5 years using public records. Marital status, educational level, and other variables in both datasets were harmonized.
Results: The Cox proportional hazards model showed that unmarried men had a higher mortality risk than married men in both countries (hazard ratio [HR] 1.47; 95% confidence interval [CI], 1.21–1.79 for Japanese and HR 1.94; 95% CI, 1.29–2.91 for Finnish); no such difference was observed in women. The highest mortality risk was observed in unmarried men with tertiary education in both Japan (HR 1.85; 95% CI, 1.21–2.83) and Finland (HR 2.21; 95% CI, 1.26–3.89), when adjusted for baseline age, health-related behaviors, and illnesses.
Conclusions: Our findings showed similarity in the combined effect of marriage and education between Japan and Finland, differing from observations in countries with more apparent socioeconomic health disparities. Further studies should examine the reasons for the excessive mortality risk in highly educated, unmarried men in both countries and consider whether selection bias led to underestimation of the true risk in unmarried older adults with lower education.